Firm Value in Indonesia's Energy Sector: Financial Performance, Ownership, Dividends, and CSR (2020 – 2023) - Febriyanti, Ni Kadek Ari; Kumalasari, Putu Diah; Endiana, I Dewa Made; Anggreni, Ni Kadek Ayu; Suadepi, Ni Luh Made Yunik (Journal of International Conference Proceedings, 2025)
This study investigates the determinants of firm value in the energy sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The research focuses on the influence of financial performance, managerial ownership, dividend policy, and Corporate Social Responsibility (CSR) on firm value. Financial performance is measured using the Debt-to-Equity Ratio (DER) and Earnings per Share (EPS). Data from selected companies were analyzed through multiple linear regression to identify the extent to which these factors contribute to firm value. The findings indicate that managerial ownership and dividend policy exert a positive and significant effect on firm value, suggesting that effective managerial control and consistent shareholder returns enhance investor confidence. Conversely, DER, EPS, and CSR show no significant influence, implying that capital structure, profitability per share, and CSR activities did not directly drive firm value in this sector during the observed period. These results highlight the importance of ownership structure and dividend strategies in strengthening firm value.